2007
DOI: 10.1021/jf0729098
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Antifungal Activity Relationship of Cinnamic Acid Derivatives

Abstract: A structure-antifungal activity relationship (SAR) study of 22 related cinnamic acid derivatives was carried out. Attention was focused on the antifungal activities exhibited against Aspergillus flavus, Aspergillus terreus, and Aspergillus niger. (E)-3-(4-methoxy-3-(3-methylbut-2-enyl)phenyl)acrylic acid (16) exhibited antifungal activity against A. niger, comparable to that of miconazole and a significant antifungal effect against A. flavus and A. terreus as well. A structure-activity relationship (SAR) study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 29 publications
2
57
0
2
Order By: Relevance
“…Our results are in agreement with the effects demonstrated by other authors in previous works related to other toxigenic fungi. Bisogno et al (2007) reported that the MIC (minimal inhibitory concentration) of caffeic acid for A. flavus, A. niger and A. terreus was >250 mg/l. Phenolic extracts of callus tissues of olive, which mainly contains caffeic acid and to a lesser extent catechin and coumarins, was inhibited by 90% aflatoxin production without inhibiting the growth of A. flavus (Nychas 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in agreement with the effects demonstrated by other authors in previous works related to other toxigenic fungi. Bisogno et al (2007) reported that the MIC (minimal inhibitory concentration) of caffeic acid for A. flavus, A. niger and A. terreus was >250 mg/l. Phenolic extracts of callus tissues of olive, which mainly contains caffeic acid and to a lesser extent catechin and coumarins, was inhibited by 90% aflatoxin production without inhibiting the growth of A. flavus (Nychas 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, many studies have pointed out the antimicrobial efficacy of certain classes of phenolic compounds, such as hydroxybenzoic acid derivatives (Lattanzio et al 1996;Amborabé et al 2002;Veloz-García et al 2010), coumaric and caffeic acid derivatives (Zhu et al 2004;Widmer and Laurent 2006;Korukluoglu et al 2008), flavonoids and coumarins (Ojala et al 2000;Ortuño et al 2006;Sanzani et al 2009a;Sanzani et al 2014), catechin, epicatechin, proanthocyanidins, andtannins (Di Venere et al 1998;Terry et al 2004;Engels et al 2009;Parashar et al 2009;Yoshida et al 2009). Moreover, some authors have studied the relationship between molecular structure and antimicrobial activity of some phenolic compounds (Lattanzio et al 1994;Amborabé et al 2002;Bisogno et al 2007). Plants contain different groups of phenolic compounds including simple phenols, phenolic acids (e.g., rosmarinic, carnosic acid), anthocyanins (delphinidin), hydroxybenzoic acids (vanillic acid), hydroxycinnamic acid (ferulic and chlorogenic acids), tannins (procyanidin, tannic acid), lignans (sesaminol), stilbenes (resveratrol), coumarins (α-coumarin), essential oil components (limonene, carvacrol-also called cymophenol, and eugenol), flavonoids (apigenin, quercetin, catechin, rutin) (Charles 2013).…”
Section: Phenolic Compounds: Natural Antimicrobials Widely Spread In mentioning
confidence: 99%
“…Our research group has used fish to assess the potential toxicity of different natural and/or synthetic novel drugs [7][8][9].…”
Section: Introductionmentioning
confidence: 99%